Is skeletal muscle echo intensity more indicative of voluntary or involuntary strength in young women?. Issue 4 (16th February 2021) - Girts, Ryan M.; MacLennan, Rob J.; Harmon, Kylie K.; Stock, Matt S.
Abstract : Echo intensity has been associated with measures of muscle strength; however, associations between echo intensity and voluntary performance assume descending drive are optimal and participants are motivated. This study aimed to compare relationships between echo intensity versus involuntary and voluntary strength. Eighteen females (age = 21 ± 2 years) participated. Echo intensity was quantified from B‐mode ultrasound images obtained from the quadriceps femoris. Isometric maximal voluntary contractions (MVC) of the knee extensors were performed, and peak involuntary strength was assessed via the interpolated twitch technique. Pearson correlation coefficients evaluated relationships between corrected echo intensity, cross‐sectional area (CSA), MVC strength, and involuntary strength. A partial correlation assessed the association between corrected echo intensity versus peak involuntary torque while controlling for CSA and MVC torque. A stepwise multiple regression model was run with echo intensity as the dependent variable. Peak involuntary torque was the single best predictor of echo intensity ( R  = 0.580, P  =  .015). Importantly, involuntary and voluntary strength were not associated ( r  = .386, P  = .126). Echo intensity was not significantly correlated with peak involuntary strength when controlling for CSA and MVC strength ( r  = −.474, P  = .074). Echo intensity is likely more closely related to involuntary strength than voluntary strength.